ANALISIS GERAK TARI LENGGER SOLASIH DI SANGGAR SATRIA KELURAHAN WONOSOBO BARAT KECAMATAN WONOSOBO KABUPATEN WONOSOBO PROVINSI JAWA TENGAH (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to describe and analyze the movements of the Lengger Solasih Dance at the Satria Studio in Wonosobo Regency. This type of research is qualitative research with descriptive and analytical methods. The main instrument in this study is the researcher himself and assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps for analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that the analysis of the movements of the Lengger Solasih Dance at the Satria Studio contains 3 parts of the variety of forward beksan, backward beksan, and beksan. Forward beksan has 10 movements, backward beksan has 12 movements, and backward beksan has 2 movements. Among the connecting movements between other movements is using the Sigetan movement. Viewed from the aspects of space, time and energy. The spatial aspect includes straight lines, diagonal lines, and curved lines. With large and medium volumes. The direction of facing front, back, right, left. Low, medium and high levels. The focus of the view is front, up, and down. In the time aspect there is tempo and rhythm. Next is the aspect of energy, in the aspect of energy there is intensity, pressure and quality. From the aspect of space, time and energy in the Lengger Solasih Dance movement, the female dancer's movements are full of dynamics in the growth period of her life, rejoicing in all her successes, and always grateful to God Almighty. The dance elements in the Lengger Solasih Dance consist of main and supporting elements. The main elements are space, time, and energy. The supporting elements are in the form of themes related to the movements of the Lengger Solasih Dance. The accompanying music adds to the joyful atmosphere in which there is a sayir that tells the story of Dewi Solasih. So, a girl looks graceful from her personality. The makeup and costume of the Lengger Solasih Dance to beautify the dancer to further support the use of properties in the form of sampur. And the performance venue is a pavilion where the dancer moves. The floor pattern used in the Lengger Solasih Dance uses a straight-line pattern. The development of movement elements such as the level and direction of the dancer's face also further clarifies the floor pattern used.